2011
DOI: 10.1021/bc100511k
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycosylation of Antibody Fragments in Escherichia coli

Abstract: Glycosylation is the predominant protein modification to diversify the functionality of proteins. In particular, N-linked protein glycosylation can increase the biophysical and pharmacokinetic properties of therapeutic proteins. However, the major challenges in studying the consequences of protein glycosylation on a molecular level are caused by glycan heterogeneities of currently used eukaryotic expression systems, but the discovery of the N-linked protein glycosylation system in the ε-proteobacterium Campylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 32 publications
(68 reference statements)
2
52
0
Order By: Relevance
“…This technology is extremely interesting for industrial applications such as the amelioration of food quality by the engineering of EPS structures or the production of engineered glycoproteins, such as vaccines and human therapeutic agents (e.g., insulin) (131,(559)(560)(561)(562)(563)(564)(565)(566)(567)(568). A better knowledge of the glycosylation mechanisms in beneficial bacteria could cause a revolution in the biosynthesis of therapeutic molecules in prokaryotic vectors.…”
Section: Discussionmentioning
confidence: 99%
“…This technology is extremely interesting for industrial applications such as the amelioration of food quality by the engineering of EPS structures or the production of engineered glycoproteins, such as vaccines and human therapeutic agents (e.g., insulin) (131,(559)(560)(561)(562)(563)(564)(565)(566)(567)(568). A better knowledge of the glycosylation mechanisms in beneficial bacteria could cause a revolution in the biosynthesis of therapeutic molecules in prokaryotic vectors.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of glycosylation sites into a protein through mutation frequently stabilizes a protein by destabilizing the unfolded state thereby coaxing the protein toward the folded state (Hanson et al 2009). The transferase reaction requires flexibility in the sequon, as the Thr/Ser residue in position 3, is required to loop around to make the Asn nucleophilic for efficient transfer (Helenius and Aebi 2004;Lizak et al 2011). This requirement favors the modification of flexible exposed regions of a protein.…”
Section: N-linked Glycosylationmentioning
confidence: 99%
“…Using the bacterial system, Lizak et al (80) demonstrated that introduction of two N-glycan acceptor sites and subsequent N-glycosylation of a singlechain antibody (scFv 3D5) with the C. jejuni N-glycan in E. coli significantly increased the proteolytic stability and solubility without influencing the affinity and serum stability of the single-chain antibody. However, N-glycosylation did not affect the overall clearance rate in the murine model system, which was probably due to the properties of the attached C. jejuni N-glycan (80).…”
Section: Vaccines Therapeutic Proteins and Novel Glycansmentioning
confidence: 99%